1999
DOI: 10.1007/s004230050220
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in pancreatic cancer - current status and future

Abstract: Although single remarkable improvements in the immunological approach to treatment of pancreatic cancer have been made, immunotherapy in pancreatic cancer is still experimental. On the basis of reliable preclinical data, new immunotherapy protocols will have to be evaluated clinically. Careful monitoring of immune responses and side effects, and assessment of quality of life will ensure identification of effective immunotherapy protocols for human pancreatic cancer in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The aim of cancer immunotherapy is stimulation of the immune system to restore its ability to recognise and respond to residual tumour cells, and it may be a useful complement to conventional anticancer strategies 1. Immunotherapy began over 100 years ago when New York surgeon William B Coley observed that malignant tumours, particularly sarcoma, regressed in patients who developed concurrent bacterial infection after surgical resection 2.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of cancer immunotherapy is stimulation of the immune system to restore its ability to recognise and respond to residual tumour cells, and it may be a useful complement to conventional anticancer strategies 1. Immunotherapy began over 100 years ago when New York surgeon William B Coley observed that malignant tumours, particularly sarcoma, regressed in patients who developed concurrent bacterial infection after surgical resection 2.…”
mentioning
confidence: 99%
“…Basing on this initial work, researchers have developed many different forms of immunotherapy, including the transfer of immune-active cells—for example, lymphokine-activated killer cells, the application of monoclonal antibodies (mAbs), the activation of specific effector cells by tumour cell lysates or extracts, and the activation of non-specific effector cells (macrophages, natural killer (NK) cells) by microbial or chemical adjuvants 1. Interestingly, instillation of viable attenuated mycobacteria—specifically BCG—is still successfully used in clinical treatment of superficial bladder cancer 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, cancer is a disease of autologous cells, and while exogenous factors such as carcinogens, mutagens, and viruses can cause cancer cells to express novel or foreign antigens, the host has already set up a significant self-tolerance to cancer cells, which is difficult to overcome, and could limit the potency of any immune response that is developed. Multiple tumor antigens have been identified in pancreatic cancer, including mucin MUC1, GA733 glycoproteins, ras peptide, EGFR, carcinoembryonic antigen (CEA), and mesothelin [25,26]. Methods to break tolerance to these tumor antigens will be critical to unlocking the potential of immunotherapy for pancreatic cancer.…”
Section: Immunotherapeutic Strategiesmentioning
confidence: 99%
“…Based on these initial results, researchers have developed various different forms of immunotherapy, including microbial and chemical adjuvants [7,8] . Interestingly, instillation of viable attenuated Mycobacteria -specifically Bacillus Calmette-Guérin -has been used successfully in current clinical treatment strategies of superficial bladder cancer.…”
Section: Inflammation and Immunity In The Tumor Environmentmentioning
confidence: 99%